Rural Tourism Development in Mountain Regions: Identifying Success Factors, Challenges and Potentials - Lun, L.; Pechlaner, Harald; Volgger, Michael (The Haworth Hospitality Press, 2016)
© 2016 Taylor & Francis.Rural tourism may act as an important driver for rural development in peripheral mountain communities that often face numerous economic, social and environmental challenges. In spite of their exceptional natural and cultural resources and heritage, they may have difficulties to take advantage of emerging dynamic processes. The present study strives to identify key success factors, risks and potentials for the development of attractive tourism products and services within rural and mountain areas. It is based on semi-structured, qualitative interviews with representatives of rural tourism best-practice initiatives across the Alps, the Apennines and the Carpathians, including case studies from Germany, Italy, Romania, Ukraine and Poland. With our analysis, we seek to contribute to the understanding of rural tourism development and management in mountain areas. Findings indicate that the integration of agriculture and tourism greatly contributes to deliver authentic tourism experiences. Moreover, leadership, inter-sectoral networks, a common orientation towards quality, as well as effective communication seem to be key success factors to overcome potential obstacles in rural tourism development.